2020
DOI: 10.3389/fmars.2020.00705
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorous Content in Blue Mussels (Mytilus spp.) Across the Baltic Sea

Abstract: To support the ongoing discussion about mussel farming and the potential to extract nutrients from the sea, this study investigated the phosphorus (P) and nitrogen (N) content of blue mussels (Mytilus spp.) under different abiotic and biotic parameters. The focus of this survey was on the highly eutrophied Baltic Sea, where salinity ranges from 4 to 27 psu, and is a major contributing factor to differential mussel growth. We observed that nutrient content was not linearly correlated to salinity, but if categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The osmotic stress based on the salinity gradient in the Baltic has the most dominant effect on blue mussel growth and health (Buer et al, 2020a;Buer et al, 2020b;Maar et al, 2015;Riisgård, Bøttiger & Pleissner, 2012;Westerbom, Kilpi & Mustonen, 2002) and therefore also on the mitigation effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The osmotic stress based on the salinity gradient in the Baltic has the most dominant effect on blue mussel growth and health (Buer et al, 2020a;Buer et al, 2020b;Maar et al, 2015;Riisgård, Bøttiger & Pleissner, 2012;Westerbom, Kilpi & Mustonen, 2002) and therefore also on the mitigation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Besides removing nutrients through biomass harvest, mussels can benefit the water transparency as a result of their filter feeding activity (Nielsen et al, 2016, Schröder et al, 2014 ) and can provide an economically interesting product. Longlines are the common practice of mussel cultivation in the Baltic ( Taylor et al, 2019 ) and, compared to bottom culture, they are most promising for nutrient removal ( Buer et al, 2020a ; Buer et al, 2020b ; Wiles et al, 2006 ; Filgueira, Grant & Petersen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient abatement costs are mainly dependent on mussel yield, which, following the salinity gradient, tends to decrease from the southwest, where mussel farming is already commercially conducted, to the northeast. However, Buer et al [99] found mussel nutrient content equally or even more dependent on habitat and harvesting time than on salinity. Besides, differences in farming and harvesting techniques, as well as investment costs and assumed lifetime of equipment may have a large impact on production costs under real farm conditions.…”
Section: Costs Of Remediating Agricultural Legacy Nutrient Loadsmentioning
confidence: 98%
“…In recent years mussel farms have been discussed as a mechanism for reducing the impact of terrestrial nutrient inputs to estuaries, through their ability to filter phytoplankton and incorporate nitrogen (N), phosphorus (P) and carbon (C) into their shells and tissue (Buer et al, 2020;Clements and Comeau, 2019;Hedberg et al, 2018;Kotta et al, 2020;Petersen et al, 2019;Rose et al, 2015). N is considered the primary limiting factor in coastal environments, although P also encourages the growth of phytoplankton (Petersen et al, 2019;Rose et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous estimates of nutrient remediation by shellfish have used a single look-up value for tissue nutrient composition applied to data from many different environmental settings (Hedberg et al, 2018;Kotta et al, 2020;van der Schatte Olivier et al, 2018). Typically, variation in tissue nutrient content due to regional or environmental factors has not been taken into account, although some work has been carried out on oysters in eastern Canada (Clements and Comeau, 2019), and on mussels in the Baltic (Buer et al 2020). The role of environmental factors on nutrient composition in mussels remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%